Validating the Conceptual Framework with Exploratory Testing - Basri, S. (Springer Verlag, 2019)
The Small and Medium Enterprises (SMEsâ) in the IT industry plays a major role towards the growth of countryâs economy. SME makes a substantial contribution towards development of the country in the form of GDP and it is widely recognized around the world. SMEs are dependent on software to accomplish their objectives and maintain survivability and sustainability in their businesses, but they often face many challenges due to various factors. Most of the SMEâs aim to produce valuable software in a short duration of time, and the traditional method of software development is not viable to provide satisfactory answer with regards to scope, time and resources they need and hence the quality of the product is not guaranteed. Though several approaches towards testing are available, adopting Exploratory testing has so far not been investigated in the context of SME, where software quality is often associated to business-critical values. In this research study, a conceptual framework using Exploratory Testing (ET) has been developed and it is validated by using Partial Least Square Structural Equation Modelling (PLSSEM). Â© 2019, Springer Nature Switzerland AG.